2011
DOI: 10.2298/gensr1101029d
|View full text |Cite
|
Sign up to set email alerts
|

Stability of yield components in wheat (Triticum aestivum L.)

Abstract: Variability and stability of yield components for the large number of divergent common wheat genotypes originated in different world breeding institutions were studied. Interaction genotype x environment has been evaluated, in different environmental conditions. The experiment was performed using randomized block design in three replications on the experimental field in different environmental conditions. A total number of 60 plants have been analyzed in the full maturity stage. The analyzed cultivars s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Significant genetic variation among spring wheat cultivars for number of spikes m −2 , as well as its differential production at test locations, have also been previously reported by Lungo et al (1990). Grains spike −1 and harvest index were found significant in other studies conducted by Ansari et al (1989) and Dimitrijevic et al (2000).…”
Section: Resultssupporting
confidence: 50%
“…Significant genetic variation among spring wheat cultivars for number of spikes m −2 , as well as its differential production at test locations, have also been previously reported by Lungo et al (1990). Grains spike −1 and harvest index were found significant in other studies conducted by Ansari et al (1989) and Dimitrijevic et al (2000).…”
Section: Resultssupporting
confidence: 50%
“…Different values of spike traits in the same cultivars in different experimental years were also found in other studies which indicated a high influence of agro-ecological factors on the expression of spike traits (Agoston and Pepo, 2005;Dakhim et al 2012). High importance in establishing a response of genotypes to environmental conditions is given to research on the stability of yield and yield components (Dimitrijević et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The grain yield of wheat depends on components such as the number of plants per m 2 , number of spikes per m 2 , number of kernels per spike, kernel weight in the spike, and the 1000kernel weight. The interactions between these parameters are complex, thus the increase in values of a single parameter decreases the value of another parameter (Laghari et al 2011;Perišić et al 2011;Dimitrijević at al. 2011;Hristov et al 2012;Milovanović et al 2012;Đekić et al 2012;Hassan et al 2013;Mohamed et al 2013;Hagos and Abai, 2013).…”
Section: The Correlation Between the Grain Yield And Some Yield Compomentioning
confidence: 99%
“…The question of the importance of the seed size is still discussed. Madić et al (2010) and Dimitrijević et al (2011) have studied variability and stability of yield components of many wheat varieties. These authors determined the significant effect of varieties, years and their interactions on the expression of traits.…”
Section: Introductionmentioning
confidence: 99%